Liberalisation And Socio-Economic Characteristics of Regional Air Passenger Travel from Nigeria to Other West Africa Countries - Adeniyi , Olufemi Oluwakoya (Corpus Intellectual, 2025)
This paper aims to examine the impacts of liberalisation on regional air passenger travel’s socio-economic characteristics within the West Africa sub-continent. It examines this impact in a two-way dimension of pre-and post-policy evaluations on socio-economic characteristics. The methodology involves using purposive sampling of the passenger who had experienced regional travel from Nigeria to other West Africa countries in the pre-and post- era. A total of 428 respondents were used in the analysis. The questionnaire was administered while the passenger was on the queue to be screened for boarding and arrival. After the passenger has confirmed to have both pre-and post-liberal regional travel experience. The analysis involves an in-dept theme descriptive analysis of policy impact in a comparative evaluation of pre-liberalisation and post liberalisation dimensionality. The study reveals that since liberalisation the passenger’s socio-economic characteristics have improved significantly. The research shows that the socio-economic trips of passenger improved significantly from Nigeria to other West African countries and vice versa. Overall, regional efforts to strengthen the system must be stepped up to bring about further benefits for socioeconomic advancement.